The Central European Manufacturin Core: What is Driving Regional Production Sharing? - Robert Stehrer; Roman Stöllinger (FIW - Research Centre International Economics, 2015)
There is evidence that Europe's manufacturing activity is increasingly concentrated in a Central European (CE) core which the IMF in a recent publication also refers to as the German-Central European supply chain. This CE manufacturing core is dominated by Germany and in addition comprises Austria and the four Visegrád countries (the Czech Republic, Slovakia, Hungary and Poland). The case of Austria is particularly interesting because it is neither the primary technology leader within the country group, nor is it an offshoring destination and therefore takes an intermediate position. This study provides further empirical evidence for the growing concentration of European industrial production in the CE manufacturing core and explores in detail the structure and development of the regional supply chains over the period 1995-2011. This includes an analysis of the impact of international production integration on the value added share of manufacturing in the economy. The econometric results point towards differentiated effects for the members of the CE manufacturing core and the remaining EU Member States. Focusing on value added generated by the manufacturing sector, the industries which build the backbone of this regional manufacturing cluster are identified. Finally, the report investigates which factors are conducive to the intensification of international production sharing. In line with the notion of a production-investment-services nexus, it is found that (inward) FDI in the manufacturing sector is associated with higher degrees of production integration. Again, the econometric evidence suggests that some of the factors explaining international production sharing, such as the level of export sophistication, have differentiated effects for the members of the CE manufacturing core as compared to the other EU countries.
Keywords: F14; F15; L16; 330; European manufacturing; production integration; global value chains; structural change